Feasibility and Diagnostic Accuracy of Brief Health Literacy and Numeracy Screening Instruments in an Urban Emergency Department. (February 2014) - Carpenter, Christopher R.; Kaphingst, Kimberly A.; Goodman, Melody S.; Lin, Margaret J.; Melson, Andrew T.; Griffey, Richard T.; Pines, Jesse
Abstract Objectives The objective was to evaluate the diagnostic accuracy of five health literacy screening instruments in emergency department (ED) patients: the Rapid Evaluation of Adult Literacy in Medicine‐Revised (REALM‐R), the Newest Vital Sign (NVS), Single Item Literacy Screens (SILS), health numeracy, and physician gestalt. A secondary objective was to evaluate the feasibility of these instruments as measured by administration time, time on task, and interruptions during test administration. Methods This was a prospective observational cross‐sectional study of a convenience sampling of adult patients presenting during March 2011 and February 2012 to one urban university‐affiliated ED. Subjects were consenting non–critically ill, English‐speaking patients over the age of 18 years without aphasia, dementia, mental retardation, or inability to communicate. The diagnostic test characteristics of the REALM‐R, NVS, SILS, health numeracy, and physician gestalt were quantitatively assessed by using the short Test of Functional Health Literacy in Adults (S‐TOFHLA). A score of 22 or less was the criterion standard for limited health literacy (LHL). Results A total of 435 participants were enrolled, with a mean (±SD) age of 45 (±15.7) years, and 18% had less than a high school education. As defined by an S‐TOFHLA score of 22 or less, the prevalence of LHL was 23.9%. In contrast, the NVS, REALM‐R, and physician gestalt identified 64.8, 48.5, and 35% of participants as LHL, respectively. A normal NVS screen was the most useful test to exclude LHL, with a negative likelihood ratio of 0.04 (95% confidence interval [CI] = 0.01 to 0.17). When abnormal, none of the screening instruments, including physician gestalt, significantly increased the posttest probability of LHL. The NVS and REALM‐R require 3 and 5 minutes less time to administer than the S‐TOFHLA. Administration of the REALM‐R is associated with fewer test interruptions. Conclusions One‐quarter of these ED patients had marginal or inadequate health literacy. Among the brief screening instruments evaluated, a normal NVS result accurately reduced the probability of LHL, although it will identify two‐thirds of ED patients as high risk for LHL. None of the brief screening instruments significantly increases the probability of LHL when abnormal.